2016
DOI: 10.1093/deafed/enw067
|View full text |Cite
|
Sign up to set email alerts
|

The Transition From Early Intervention to School for Children Who Are Deaf or Hard of Hearing: Administrator Perspectives

Abstract: Although the transition from early intervention (EI) to school is a significant milestone in the lives of young children, little research to date has investigated this transition among children who are deaf or hard of hearing (D/HH). The aims of this study were to investigate the organizational policies, procedures, and guidelines that facilitate or hinder the transition from the EI system to the school system for children who are D/HH from the perspective of program administrators. Using the Enhanced Critical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…The role of EI professionals in the transition to school is crucial. They often act as a liaison between families and schools by providing families with information on school systems and classroom expectations, contacting school district personnel to provide information about the incoming student, and facilitating transition meetings (Curle et al, 2016;Rous, Myers, & Stricklin, 2007).…”
Section: Ei Professionalsmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of EI professionals in the transition to school is crucial. They often act as a liaison between families and schools by providing families with information on school systems and classroom expectations, contacting school district personnel to provide information about the incoming student, and facilitating transition meetings (Curle et al, 2016;Rous, Myers, & Stricklin, 2007).…”
Section: Ei Professionalsmentioning
confidence: 99%
“…Curle (2015) examined Internet-based information available on the transition to school for D/HH children, and found that while most school districts and EI programs have policies or practices in place to smooth the transition from EI to school, few offer information that is easily accessible to families via the Internet, and even fewer have information that is specific to D/HH children. Administrator perspectives on the transition to school for D/HH children were investigated by Curle et al (2016). They found that one of the most important facilitators of transition was fluid communication between all stakeholders.…”
Section: Ei Professionalsmentioning
confidence: 99%
“…Transitioning from EI to academic settings can be difficult because a school's primary focus is on the academic and social performance of the child. 44,45 The EI and education systems may not be congruent, (ie, separate oversight agencies, distinct funding sources, and disparate data systems). Linked state databases provide a comprehensive data system to address the short-and long-term outcomes for children served in a state EHDI program.…”
Section: Ei and School Readinessmentioning
confidence: 99%
“…Children may transition into a variety of classroom settings, including inclusive, self-contained, full-day, and half-day programs (Pang, 2010). The options available for families are often a major factor in families’ decisions on whether to send their child to a school-based program (Brandes et al, 2007; Curle et al, 2017; Pang, 2010). To help families understand their classroom setting options and select a preferred placement, educators should share information with families before and during the initial IEP meeting regarding the details of classroom options.…”
Section: Preparing Familiesmentioning
confidence: 99%
“…Families often perceive the change from the natural environment service delivery of early intervention for infants and toddlers to the more structured Part B Section 619 (i.e., hereafter referred to as Part B) school settings for preschoolers as challenging. Families have reported challenges such as not understanding the transition process, being offered limited options, and not understanding the differences in service delivery (Curle et al, 2017; Mawdsley & Hauser-Cram, 2013). These challenges can leave families feeling worried, frustrated, and stressed (Brandes et al, 2007; Mawdsley & Hauser-Cram, 2013).…”
mentioning
confidence: 99%